2016
DOI: 10.3324/haematol.2016.150334
|View full text |Cite
|
Sign up to set email alerts
|

Upfront autologous stem cell transplantation for newly diagnosed elderly multiple myeloma patients: a prospective multicenter study

Abstract: T he feasibility and efficacy of high-dose melphalan followed by autologous hematopoietic stem cell transplantation in newly diagnosed elderly patients with multiple myeloma was analyzed prospectively. Fifty-six multiple myeloma patients, aged 65 years or over, from 6 French centers were studied. The induction therapy was bortezomib-based in combination with dexamethasone and either thalidomide, cyclophosphamide or lenalidomide, for 4-6 cycles. Peripheral blood stem cells were collected after high-dose cycloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 32 publications
5
42
1
3
Order By: Relevance
“…A much smaller French multicenter trial in ≥65 year old patients used bortezomib-© Ferrata Storti Foundation based induction, MEL140 in 18 (36%) and MEL200 in 32 (64%) patients and consolidation with either Rd or bortezomib-based treatment, confirming the safety and efficacy of ASCT as first-line treatment in elderly MM patients. 17 Although this study was not sufficiently powered to pick up differences between the two melphalan schedules, and the median follow-up, at 21 months, was shorter, the estimated PFS and OS rates at 2 years were encouraging with 76% and 88%, respectively, suggesting that MEL200 may induce superior PFS and OS rates in elderly patients. Nevertheless, since this was a non-randomized study and patients were selected (e.g., those with MEL200 were fitter and not comparable to all newly diagnosed elderly MM patients), objective, prospective and proficiently performed fitness tools might be of benefit before intensive treatment is induced, the more so, since patients and physicians fitness ratings are not as objective as defined tests and scores.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…A much smaller French multicenter trial in ≥65 year old patients used bortezomib-© Ferrata Storti Foundation based induction, MEL140 in 18 (36%) and MEL200 in 32 (64%) patients and consolidation with either Rd or bortezomib-based treatment, confirming the safety and efficacy of ASCT as first-line treatment in elderly MM patients. 17 Although this study was not sufficiently powered to pick up differences between the two melphalan schedules, and the median follow-up, at 21 months, was shorter, the estimated PFS and OS rates at 2 years were encouraging with 76% and 88%, respectively, suggesting that MEL200 may induce superior PFS and OS rates in elderly patients. Nevertheless, since this was a non-randomized study and patients were selected (e.g., those with MEL200 were fitter and not comparable to all newly diagnosed elderly MM patients), objective, prospective and proficiently performed fitness tools might be of benefit before intensive treatment is induced, the more so, since patients and physicians fitness ratings are not as objective as defined tests and scores.…”
mentioning
confidence: 82%
“…Moreover, immunotherapy to stimulate antitumor immunity after ASCT is of particular interest, since T cell exhaustion has been identified as a distinguishing feature of relapse after ASCT. 5 The pipeline of promising new treatments raise hopes for continuous improvements, the Straka 12 and Garderet 17 trials demonstrating another essential treatment element, how this can be achieved in elderly patients.…”
Section: Referencesmentioning
confidence: 99%
“…In the DSSM II trial, in which patients underwent tandem ASCT conditioned with melphalan at 140 mg/m 2 , no difference in terms of TRM (1%) was reported between patients aged 60 to 65 years and those older than 65 years . In another prospective trial comparing melphalan at 140 mg/m 2 with melphalan at 200 mg/m 2 in patients older than 65 years, the TRM rate at day +100 from transplantation was 0% in both arms, and this confirmed the feasibility of delivering high‐dose melphalan to older patients …”
Section: Sct For Patients With Newly Diagnosed Myelomamentioning
confidence: 77%
“…16 In another prospective trial Cancer August 1, 2019 comparing melphalan at 140 mg/m 2 with melphalan at 200 mg/m 2 in patients older than 65 years, the TRM rate at day +100 from transplantation was 0% in both arms, and this confirmed the feasibility of delivering high-dose melphalan to older patients. 17 Many studies have confirmed that chronological age is not itself a limitation for ASCT. Instead, organ function and comorbidities as well as the performance status should be taken into consideration to define ASCT eligibility, 18 and currently in the United States, ASCT is considered and may be appraised for patients up to the age of 80 years ( Fig.…”
Section: Asct Eligibilitymentioning
confidence: 99%
“…There is no consensus in the MM community, as some authors defend the use of an intermediate dose of 100 or 140 mg/m 2 demonstrating equal efficacy in CR rates, EFS, or OS but with lower toxicity [9, 14, 33, 35, 38] or even lower TRM [39]; other authors are in favor of MEL200 as they did not find any excessive toxicity or worse disease outcomes [11, 32, 40]; and others conclude that reduced doses of melphalan can benefit selected cases, but higher doses are preferred [13, 30]. A recent prospective French study [36] demonstrated that there was no difference in myelotoxicity, infections, TRM, or disease response between MEL200 and MEL140, but it was noticed that patients treated with MEL200 had better EFS rate. In our analysis, even though it was not statistically significant, we also noted a trend to a better EFS rate in MEL200 elderly patients when compared to elderly patients treated with reduced doses of melphalan (62 months vs 45 months).…”
Section: Discussionmentioning
confidence: 99%